Os desafios entre a drenagem urbana e os resíduos sólidos : o caso de Aracaju/SE - Pereira, Frances Doglas de Santana (2015)
The planning of urban management permeates shares in the field of environmental sanitation. Knowledge of management models used by municipalities is essential for the assessment of urban functions. In view of this the present study is meant to examine the importance of urban management in an integrated manner, in order to propose measures for the integrated solid waste management and urban drainage. To meet the main objective the following specific objectives were: to identify the problems of improper disposal of solid waste in urban drainage systems and their impacts; analyze the laws and rules relating to solid waste and urban drainage; diagnose the current situation of solid waste and urban drainage in Aracaju/SE and propose integrated management measures of solid waste and urban drainage. Therefore the following methodological procedures were adopted: literature; questionnaires and field research, with further processing. From the results obtained it was found that the urban drainage and solid waste systems are interconnected , and the malfunction of the solid waste management greatly affects the efficiency of drainage systems , and that fragmentation of sanitation services, without which they interact, affect the urban management. Thus, inadequate urban planning is responsible for environmental impacts in cities, combined with indifference by the population on common community issues.